E-Business Innovation on SME Resilience Model: The Moderating Role of Financial Literacy - Wiwin Rosmawati; Loso Judijanto; Amilusholihah; Encep Sopandi; Zainal Arifin; Fandi Achmad (Journal of Economics, Business, & Accountancy Ventura, 2025)
In the era of advanced digitalization, the ability of SMEs to adapt and adopt e-business innovation is a key factor to survive and compete in the global market. This study aims to determine the effect of e-business innovation in improving the resilience of SMEs and explore the extent to which financial literacy moderates the relationship between the adoption of e-business innovation and SME resilience. This research was conducted in the printing sector of Malang City, Indonesia, which has around 2,145 printing SMEs based on data from the Malang City Cooperative Office in 2023. The research method uses a quantitative approach with a Structural Equation Model (SEM) assisted by the Smart PLS application. The sampling technique used purposive sampling with a sample of 100 SMEs selected based on criteria such as business size, level of e-business technology adoption, and financial literacy. The results showed that the variables studied had a significant and positive effect so that it was accepted. In addition, strong financial literacy can strengthen the relationship between e-business innovation and SME resilience. These findings underscore the importance of improving financial literacy among SMEs as part of the strategy to maximize the benefits of ebusiness innovation in improving SMEs' business resilience.